Pengaruh Independensi Dewan Komisaris, Komite Audit, Dan Internal Audit Terhadap Fee Audit Eksternal (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2012-2014) - Anandita, Arnes; Wiliasti, Arlinia (Universitas Merdeka Madiun, 2020)
Abstractâ€” This study aims to provide empirical evidence of the influence of: Good Corporate Governance (Board of Commissioners Independence, Audit Committee Independence, Audit Committee Size, Audit Committee Meeting Intensity and Internal Audit) on External Audit Fees in Manufacturing companies listed on the Indonesia Stock Exchange in 2012- 2014. This research was conducted using secondary data. The population in this study were 30 manufacturing companies listed on the Indonesia Stock Exchange (BEI) during the 2012-2014 period. The analysis method used is multiple linear regression analysis by first doing data descriptions, classical assumption tests which include normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, and hypothesis testing used are t-test, F-test, and Adjusted R. Square. The results of this study prove that the independence of the board of commissioners and internal audit variables has an effect on external audit fees, while the audit committee independence variable, the size of the audit committee and the intensity of audit committee meetings have no effect on the external audit fees in manufacturing companies listed on the IDX for the 2012-2014.Â Keywordsâ€”: Independence of the board of commissioners; independence of the audit committee; audit committee size; intensity of audit committee meetings; internal audit.